How online video platforms could support China’s independent microfilm (short film) makers and enhance the Chinese film industry - Gilardi, Filippo; White, Andrew; Cheng, Shuxin; Sheng, Jin; Song, Wei; Zhao, Yifan (2019)
As with the US and EU media landscapes, the Chinese film industry is dominated by platforms similar to Netflix, Hulu and Amazon, most notably in the form of the BAT (Baidu, Alibaba, Tencent) companies that according to He (2015) are ‘taking over the film industry’. These have been described as ‘imperialistic’ in the monopolization of their respective markets and in the use of their financial muscle to squeeze content creators’ incomes (Jin, 2015). While in the western market this undermines the mainly middle-class professionals who drive creativity (Timberg,2015), in China it limits the opportunities for new talent to grow. This paper will, therefore, give an overview of the Chinese microfilm (online short movies) industry and investigate how Chinese BAT companies and other online video providers could enhance the Chinese film industry by developing infrastructure to direct revenue of microfilms to the creators.